(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Lipoprotein is a bacterial cyclic surface active compounds produced mainly by different microorganism like bacteria, fungi and yeasts as secondary metabolites, fourty eight bacterial isolates were obtained from 20soil samples that oils contaminated from various location in Al-Najaf City.